What evidence is there for implicating the brain orexin system in neuropsychiatric symptoms in dementia? - Bergamini, Giorgio; Coloma, Preciosa; Massinet, Helene; Steiner, Michel Alexander (Frontiers in Psychiatry, 2022)
Neuropsychiatric symptoms (NPS) affect people with dementia (PwD) almost universally across all stages of the disease, and regardless of its exact etiology. NPS lead to disability and reduced quality of life of PwD and their caregivers. NPS include hyperactivity (agitation and irritability), affective problems (anxiety and depression), psychosis (delusions and hallucinations), apathy, and sleep disturbances. Preclinical studies have shown that the orexin neuropeptide system modulates arousal and a wide range of behaviors via a network of axons projecting from the hypothalamus throughout almost the entire brain. It does so by integrating different types of incoming information (e.g., metabolic, circadian, sensory, emotional) and converting them into the required behavioral output. Here we present an overview of the behavioral domains influenced by the orexin system that may be relevant for the expression of some critical NPS in PwD. We also hypothesize on the potential effects of pharmacological interference with the orexin system in the context of NPS in PwD.